Analisis Perlakuan Akuntansi Atas Produk Rusak Galon 19L Pada PT. Aqua Golden Mississipi Babakanpari - Mevia, Tasya Arta; Afif, M.Nur; Melani, Maria Magdalena; Anwar, Saepul (Jurnal Ilmiah Raflesia Akuntansi, 2024)
Analyzing the accounting for damaged products is important for the Company to calculate the cost of production. The purpose of this research is to determine the recording and calculation of production costs, determine the causes of damaged products, and calculate the accounting treatment for damaged products when determining the production costs of 19L gallons at PT. Aqua Golden Mississippi Babakanpari. The research method used is descriptive with a quantitative approach. Data collection methods include interviews, field observations, and documentation. The data analysis technique uses a full costing approach, process costing method, and determining the cost of production. These findings explain the production costs set by PT. Aqua Golden Mississipi Babakanpari Rp. 15,383,945,347,-. The total loss of damaged products was IDR. 2,631,937,174,- recorded as controlling factory overhead costs.